SEKSUALITAS PEREMPUAN DALAM NOVEL NYAI GOWOK KARYA BUDI SARDJONO: SEBUAH KAJIAN KRITIK FEMINIS RADIKAL - Oni Sumiati; Martono Martono; Djon Lesmono (Universitas Tanjungpura, 2019)
AbstractThe women are people who can attract the men easier. Their attractiveness always be dicussed by the men. It is not about their beauty and intellectual but it focuses on the sexuality casses. In this research, the reseracher focused on the women sexuality which taken from a novel entittled Nyai Gowok by Budi Sardjono. The research problem including of sexuality abusive by men and women’s of ptriachal. The researcher used descriptive qualitative method in order to analyze the data. The data source is taken from a novel itself in 330 pages. The techniqueof colleecting the data used documentary study technique where the tools of the research are any or some person (human), the researcher itself tland also the result of the research showed that sexual assault had been done by the men such as rape, sexual, exploitation (like porn/ prostitution), sex slavery and the compulsion of abortion. Moreover, the womens opposition patriarchal domination is about the effort by giving the understanding, how to refuse, state the opinion and how to end the marriage strategically. The novel of Nyai Gowok can be used as the learning materials. Of indonesian language and literature in order to analyze the intrinsic and extrinsic substances of indonesian novel or novel translation. Keywords: patriarchal, radical feminism criticism, sexuality.